2012
DOI: 10.1039/c2em30699a
|View full text |Cite
|
Sign up to set email alerts
|

Sampling, extraction and measurement of bacteria, endotoxin, fungi and inflammatory potential of settling indoor dust

Abstract: Selection of sampling device, sampling location and period are important first steps in the measurement of exposure to bioaerosols in indoor air. The steps following the sampling include treatment of samples and laboratory analysis. In this study, settling bacteria, endotoxin, fungi and serine protease have been measured in Danish homes using Electrostatic Dust Fall Collectors (EDCs). The effects of the presence of occupants, sampling on open surfaces versus in bookcases and treatment of samples have been stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
79
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 71 publications
(85 citation statements)
references
References 48 publications
5
79
1
Order By: Relevance
“…In another study differences in endotoxin exposures have been found when occupants were absent from their home for two weeks. During occupancy the levels of endotoxin were 650 EU m À2 day À1 while during occupant absence the levels dropped to 39 EU m À2 day À1 (average values) [35]. Thus, the presence of occupants seems to increase the concentration of airborne endotoxin considerably.…”
mentioning
confidence: 92%
See 4 more Smart Citations
“…In another study differences in endotoxin exposures have been found when occupants were absent from their home for two weeks. During occupancy the levels of endotoxin were 650 EU m À2 day À1 while during occupant absence the levels dropped to 39 EU m À2 day À1 (average values) [35]. Thus, the presence of occupants seems to increase the concentration of airborne endotoxin considerably.…”
mentioning
confidence: 92%
“…However, studies comparing the indoor and outdoor levels of bacteria often find the indoor/ outdoor ratios are above 1 [2,6,21,34,52], showing the importance of indoor sources. Several studies have suggested that in environments like homes [35], university buildings [37], schools [6] and day-care centers [4], the main source of airborne bacteria indoors are humans and human activities. Bacterial exposure levels in homes are influenced by many factors, including, for example, relative humidity of indoor air and seasons during the year [22,44].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations